The Effect of Providing Nutrition Education with Media Booklets on Increasing Knowledge and Attitudes of Young Girls about Anemia at SMPN 36 Samarinda - Elly Nardyawati; Aminah Toaha; Nino Adib C (Journal of Educational Analytics, 2023)
Anemia is a condition where the number of red blood cells or hemoglobin levels in red blood cells are below normal limits. The prevalence of anemia in young women in Indonesia, based on the 2018 Riskesdas data, is 48.9%. The purpose of this study was to determine the effect of providing nutrition education using booklets on increasing the knowledge and attitudes of young women about anemia at SMPN 36 Samarinda. This research method is quasi-experimental (quasi-experiment), and the sampling technique is a purposive sampling technique consisting of 36 respondents using a questionnaire. The results showed that there was a significant difference in the knowledge of young women after being given nutrition education between the use of media in the experimental group and the control group with a p-value of 0.008 (p <  0.05), and there was no significant difference in the attitude of young women after being given nutrition education between the use of media in the experimental group and the control group with a p-value of 0.291 (p <0.05). There is an effect of providing nutrition education using booklets and PowerPoint media on increasing knowledge, but it does not affect the attitude of respondents.